Development of Student Worksheet Based on Project Based Learning on Mixed Separation Material at SMKN 7 Pontianak - Purba, Nasriani; Harun, Andi Ifriany; Ulfah, Maria; Enawaty, Eny; Rasmawan, Rahmat (Universitas Pendidikan Mandalika, 2024)
Chemistry learning in schools still tends to be teacher-centered, so students have limitations in connecting subjects to real life. The material on the mixed separation related to basic competence skills will be achieved through chemical experiments, but there is no chemical laboratory in schools. The learning activities only use textbooks borrowed from the library, so there is a need for other teaching materials that can help students to carry out chemistry experiments in the form of PjBL based Student Worksheet (LKPD) on separating mixed. The aim of this research is to asses the feasibility of PjBL based LKPD in mixed separation and determine the responses of students and teachers. Research and development (R&D) uses the ADDIE model, but this research only reaches the development stage. The subjects in this study were PjBL-based worksheets on mixed separation materials which were tested on a limited basis (15 students) and a large scale (35 students) at State Vocational High School (SMKN) 7 Pontianak. Data collection techniques used are direct communication techniques and indirect communication. Data collection tools are interview guides, feasibility assessment sheets, student and teacher response questionnaires. The expert assessment using the Gregory test showed that the criteria were very feasible, with a very high validity value of 1.00 for content, presentation, graphics and language aspects. The response test results with limited and extended trials obtained an average percentage of 85% and 86% respectively, and the response test results for 3 teachers obtained an average percentage of 88%. The results of the assessment indicate that the PjBL-Based Student Worksheet (LKPD) is very suitable for use in supporting chemistry experiments on mixed separation material in learning activities.